ANALISIS LOYALITAS KONSUMEN CAFE EXCELSO CILANDAK TOWN SQUARE - Risma Ayu Fiana, - (2019)
This research is a quantitative research that aims to determine the effect of price and quality on consumers loyalty at Cafe Excelso. The population in this research were 4000 consumers or visitors who came to Excelso Cilandak Town Square. The sample size taken was 98 respondents, with a non probability sampling method. data collection is done through questionnaires. The technical analysis used is the PLS (Partial Least Square) analysis method. The results of the research shows that (1), prices have a significant effect on consumer loyalty with a path coefficient of 0.506 (2), service quality has a significant effect on service quality with a path coefficient of 0.490.